The importance of identifying environmental factors for stuttering treatment in monozygotic twin girl - Dimoski, Sanja M.; Tepšić Ostojić, Vesna J. (Vojnosanitetski pregled, 2021)
Introduction. Stuttering is a speech disorder and its etiology is an interplay of genetic and environmental factors. Despite the absence of definite etiology understanding, there are numerous available treatments for stuttering. For some adult patients, the contemporary concept includes psychotherapist involvement concomitant with speech therapist. Case report. A 24-year-old girl, who is a monozygotic twin, has been stuttering from early childhood, while her twin sister has never exhibited a speech disorder. Since the role of genetic factors was evident (father stuttered too), the focus of this report was on environmental factors of physical and psychological development (slow development), as well as family psychodynamics (divorce of parents in early adolescent period and criticizing from her father forstuttering). The patient, as well as her family members, denied the significance of the symptoms, which could also explain the absence of early treatment. Conclusion. Unfavorable conditions of psychological development, as well as family psychodynamics could explain speech therapy starting at the age of twenty-four and being insufficient for symptom overcoming. Psychotherapy is indicated in the integrative part of treatment in this case of speech disorder.
Keywords: family; genetics; parent-child relations; psychotherapy; risk factors; speech disorders; stuttering; twins